Economic and procedural status of the Prosecutor in conditions of domestic legislation recodification - Волевський, Лев Володимирович (Theory and practice of jurisprudence, 2019)
The article highlights the changes in the procedural position of the prosecutor as a subject of economic and procedural relations. At the same time, attention is paid to the causes and conditions of recodification as a form of systematization of economic procedural legislation. It is noted that the general conditions of recodification are connected with the necessity to amend, among other things, of the procedural and legal status of the subjects of economic and procedural relations. In addition, the issues of correlation of the prosecutor’s participation in the economic process with the principle of proportionality, the change of the purpose of the prosecutor’s participation in the stated proceedings are considered. Besides, the subject of the research in the article includes the manifestation of the prosecutor’s economic procedural legal capacity in various forms of his participation in the economic procedure: appeal to the court, entry into a court case; the specifics of the appeal against the decision by the prosecutor and the restrictions imposed by the legislator in connection therewith. As a prerequisite for the participation of the said entity in the economic proceedings, it is argued that there is a need for the legislative fixing of the obligatory registration of the official e-mail address in a single judicial information and telecommunication system